Reviving the Arabic Language Instinct: A Psycholinguistic and AI Synergy - Hanifansyah, Nur (Al-Wazan: Journal of Arabic Education, 2025)
The integration of artificial intelligence (AI) in education has sparked new possibilities for enhancing language acquisition; however, its rapid advancement poses challenges when not harmonized with cognitive and psychological readiness. This study investigates how psycholinguistic principles, when paired with AI tools, can foster the development of Arabic language instinct among advanced learners. The research focuses on 50 participants from Pondok Pesantren Darullughah Wadda’wah, utilizing a mixed-methods approach that combines quantitative data collection with qualitative classroom observations and interviews. The results show significant linguistic improvements: grammar proficiency increased from 68% to 85%, vocabulary retention improved by 40%, and learners’ speaking confidence rose by 30%. A critical finding of this study is the role of dzauq—a form of linguistic and cultural intuition—in enhancing language depth and sensitivity. AI-based applications, such as adaptive feedback systems and speech simulators, proved effective in improving learner engagement, responsiveness, and self-correction capabilities. Nonetheless, the tools still face limitations, especially in accurately capturing dialectal variety and cultural semantics inherent in Arabic. This research contributes to the growing body of literature on language pedagogy and artificial intelligence by proposing a model that integrates psycholinguistic insight with AI-enabled learning. It highlights the necessity of balancing technological advancement with human-centered strategies rooted in linguistic identity and cultural authenticity. Ultimately, the study offers a transformative framework for Arabic language education that prioritizes both intuitive fluency and ethical, context-aware technology integration.